Maintaining Connections: An Exploratory Analysis of the Predictors of Prison Visitation with Children and the Post-Release Plans of Incarcerated Mothers - Smith, Wesley T. (Women & criminal justice, 2022)
Parental incarceration has been found to negatively impact families and communities. This study examined characteristics that impact receiving in-person visits among a sample of incarcerated mothers of minor children in a large Southern prison system. Factors impacting post release plans to live with children were also examined. Contact with their children, race/ethnicity, offense type, previous incarceration, and sentence length predicted whether incarcerated mothers received in-person visits from their children. Receiving visits from their children, race/ethnicity, having custody prior to arrest, and offense type predicted whether incarcerated mothers planned to live with their children after release from prison. Implications for policy and future research are presented.